Economic Update for Cote d'Ivoire : Cacaoland - How to Transform Cote d'Ivoire - World Bank Group (World Bank, Washington, DC, 2019)
Cocoa is essential to Cote d’Ivoire. This sector mobilizes close to one million producers who provide income to five million persons (one-fifth of the country’s population) in order to meet 40 percent of global supply. Cocoa is also the country’s leading foreign exchange earner and is among the sectors making the biggest contribution to government revenue. In short, cocoa plays a central role in Ivorian society and in the lives of many families. However, despite its importance to the Ivorian economy and society, the cocoa sector is not fully playing its role as the engine of economic development. Some even go so far as to cite the curse of “brown gold,” for at least three reasons. First, more than half of producers live below the poverty line—on less than CFAF 757 (roughly 1.2 US Dollar) a day. Second, the price paid for the expansion of cultivated areas in recent decades has been the destruction of virtually all the country’s forests. Third, Côte d’Ivoire has not yet managed to increase its share (between 5 and 7 percent) of the profit made along the cocoa-chocolate global chain. Given this situation, it is not surprising that cocoa is at the center of a host of economic policy discussions in Côte d’Ivoire and that the Government has sped up its deliberations aimed at improving the performance of the sector, in particular through the Abidjan Declaration signed jointly in 2018 by the Presidents of Côte d’Ivoire and Ghana, which seeks to harmonize their policies and thus maximize their profit (these two countries account for approximately 65 percent of global production). After analyzing the most recent trends in the Ivorian economy, this ninth economic update for Côte d’Ivoire therefore focuses on how the cocoa sector could support the structural transformation of the country and, in so doing, promote greater economic and social inclusion.